Transitions and Motivations for Substance Misuse in Prison Inmates With ADHD and Conduct Disorder: Validation of a New Instrument. Issue 2 (3rd April 2017) - Young, Susan; González, Rafael A.; Wolff, Kim; Mutch, Laura; Malet-Lambert, Isabella; Gudjonsson, Gisli H.
ABSTRACT: Objective : There is a reasonable theoretical base for understanding the possible causes and motivations behind substance misuse and its dependency. There is a need for a reliable and valid measure that delineates the markers of substance use from its initiation and identifies different motivations for drug use transitioning, maintenance, and dependency. We addressed this gap in the United Kingdom by examining and validating the Substance Transitions in Addiction Rating Scale (STARS).Methods : For this review, 390 male prisoners were screened for conduct disorder and assessed with a clinical diagnostic interview for attention deficit/hyperactivity disorder (ADHD). They completed the four STARS subscales regarding their substance use. Exploratory structural equation modeling was performed to assess the STARS structure and to derive factors to assess validity against ADHD and conduct disorder diagnostic categories.Results : Each of the subscales produced meaningful and reliable factors that supported the self-medication and behavioral disinhibition hypotheses of substance use motivation. The findings robustly show that ADHD is significantly associated with the need for coping as a way of managing primary and comorbid symptoms, but not conduct disorder. The findings were strongest for the combined ADHD type.Discussion : STARS has a great potential to further the understanding of the motivation behind substance use and its dependency in different populations.